Strategi Komisi Independen Pemilihan (KIP) dalam Meningkatkan Partisipasi Gen Z Pada Pemilu dan Pilkada Kota Banda Aceh Tahun 2024 - Nofriadi, Ilmu Pemerintahan, Universitas Syiah Kua; Afra, Raisatul; Rachman, Ananta Mulya; Anwar, Muhammad Nafis; Manatnine, Annisa Ara; Nugraha, Dio Ananda; Helmi, Helmi (Jurnal Politik dan Pemerintahan Daerah, 2025)
This study aims to analyze the political participation of Generation Z (Gen Z) in Banda Aceh during the 2024 general and local elections, focusing on the factors that influence their engagement and the role of the Independent Election Commission (KIP) in enhancing participation. Using a descriptive qualitative approach, data were collected through in-depth interviews with Gen Z university students and KIP members. The study applies Milbrath and Goel’s theory of political participation as well as Campbell et al.’s theory of voter behavior to examine the dynamics of Gen Z involvement. The findings reveal that Gen Z demonstrated higher participation in the local elections (Pilkada) than in the general elections (Pemilu), driven by emotional closeness to local candidates and the relevance of regional issues. Additionally, KIP Banda Aceh successfully increased Gen Z participation through communicative and adaptive outreach strategies, such as campus-based activities and the use of social media platforms that align with Gen Z’s daily lives. This research recommends the development of more participatory and contextual political communication strategies to further strengthen Gen Z's involvement in the democratic process, particularly in the context of local democracy in Banda Aceh.